Effects of the flexible exchange rate system on developing countries - Hans-Peter Nissen; Klaus Behling (Intereconomics, 1981)
The Bretton Woods system of fixed exchange rates was abandoned by the industrialised countries in March 1973. They switched to a system of flexible exchange rates. Representatives of the developing countries were particularly critical of the industrialised countries' exchange rate flexibility. They saw themselves not only bearing the brunt of the costs associated with balance of payments readjustments but also faced with greater fluctuations both in prices and terms of trade and with other negative effects due to the general increase in uncertainty regarding exchange rates. Are such fears justified?
Keywords: 330; Exchange Rates